STANDAR GLOBAL PENDIDIKAN PEKERJAAN SOSIAL DAN KRITIK TERHADAP KURIKULUM PENDIDIKAN PEKERJAAAN SOSIAL DI INDONESIA - Adi Fahrudin (Sosio Informa, 2004)
Global Standard on Social Work Education and Suggestion to the Curriculum of Social Work Education in Indonesia.Global change and trends toward industrialization and privatization have encouraged transformation and social institutions. Therefore, this has been a growing need to reform curriculum for social work education in Indonesia, it was suggested that competency based social work education would be appropriated to the current social situation in Indonesia.